Managing Schema of Knowledge Acceleration Estimator (KAE) Model to Customer Behavior Using Business Metrics - Syah, Rahmad; Nasution, M.K.M.; Elveny, Marischa; Nababan, Erna B; Sembiring, Sajadin (ExcelingTech, 2020)
Business metrics in Financial Technology 1500 users spread across North Sumatera Province. The impact of commercial digital business (commercial enterpreneurship and social entrepreneurship) is very large on users who are currently increasing in number. To produce Knowledge Acceleration (KAE) Model using Business Metrics on the impact of Commercial Entrepreneurship and Social Entrepreneurship in their utilization.Uncertainty arising from sustainable business operators by considering aspects of Business Metrics related. MARS an linear regression analysis method nonparametrics intended for statistics with the aim of facilitating research and modeling the relationships of each of the multi variables that arise